Liquid Smoke as Fat Protector and Its Effect on Rumen Fermentation Characteristics and Microbial Activity - N. C. Tiven; L. Hartati; T. M. Simanjorang (Tropical Animal Science Journal, 2021)
This study was conducted to determine the effect of liquid smoke as a fat protector on unsaturated fatty acids (UFAs) and its effect on rumen fermentation characteristics and microbial activity. Crude palm oil (CPO) was mixed with Prosteo skim milk (1:2), then divided into three treatments i.e., crude palm oil without protection by liquid smoke as a control (P0), crude palm oil protected by 2.5% of liquid smoke (P1), and crude falm oil protected by 5.0% of liquid smoke (P2). For in vitro testing, 300 mg of the feed substrate (elephant grass and bran with the ratio of 60:40) was added with 5% of each crude palm oil preparation of P0, P1, and P2 and put in a fermentor syringe. Then, 30 mL of the mixture of rumen fluid and buffer-minerals solution (1:2) was added into each syringe fermentor and flushed with CO2. The fermentor syringes were incubated in a water bath at 39ᵒC for 48 hours. Variables measured were fatty acid composition, fermentation characteristics, and rumen microbial activity. The data were analyzed by the analysis of variance with a completely randomized design. The results showed that the protection of CPO with liquid smoke in P1 and P2 groups decreased saturated fatty acids (SFAs), but increased (p<0.01) monounsaturated fatty acids (MUFAs), polyunsaturated fatty acids (PUFAs), and CMCase activity. Protection of CPO with 2.5% of liquid smoke (P1) significantly increased (p<0.01) fermentation characteristics (NH3 content and pH). It can be concluded that the use of 2.5% of liquid smoke has a better effect on feed fats protection, because it can reduce hydrogenation, increase UFAs, and has no negative effects on fermentation characteristics and microbial activity.